On the mammals collected by Friedrich Sellow in Brazil and Uruguay (1814–1831), with special reference to the types and their provenance - Garbino, Guilherme S. T.; Nogueira, Marcelo R. (Zootaxa, 2017)
From 1814 to 1831, the Prussian naturalist Friedrich Sellow collected 263 mammals in Brazil and Uruguay. Upon receiving the specimens, the curator of the Berlin Zoological Museum, Martin Lichtenstein, removed the original labels and replaced with ones containing more generalized locations. As a consequence, several type specimens have now dubious type localities. We examined these types as well as geographically restricted mammals collected by Sellow. In some cases, there are inconsistencies between the specimen label and the collection catalog regarding the collecting locality. We conclude that the locality information on the lectotype of the tent-making bat Uroderma bilobatum is mistakenly identified, and therefore, we restrict it to “eastern Brazil”. We designate a lectoype for Azara’s agouti, Dasyprocta azarae, and restrict its type locality to the region travelled by Sellow in São Paulo. Although there are no recent records of the woolly giant rat, Kunsia tomentosus, from its type locality, the species may have been recently extirpated from the area. Two primate specimens supposedly collected by Sellow, a silvery marmoset, Mico argentatus, and a black tamarin, Saguinus niger, occur only in the Amazonia of northern Brazil, outside the route travelled by the naturalist, and are more likely to have been collected by Sieber. Our investigations stress the importance of collecting vouchers for verifying species occurrence records and establishing a solid taxonomy.